Senior workers retirement and inter-generational transfer of competencies: critical issues and opportunities for italian smes - Berdicchia, Domenico (Piccola Impresa / Small Business, 2013)
This article concerns the intergenerational transfer of competencies in the SMEs withinthe traditional “Made in Italy” sector, with a specific focus on the clothing and footwear industries. These companies based their competitiveness on a relevant set of competencies which is becoming increasingly at danger because of the imminent retirement of the baby boomer generation of workers. In this contribution work we report some of the outcomes of a European research project, with a specific attention on the critical aspects and difficulties that SMEs are facing in order to manage senior workers’ competencies and the possible advantages that a more focused effort toward such direction might bring. With a typical action-research approach, we first describe the risks that the retirement of senior workers may imply for the companies in terms of depletion of their competencies; then, with a specific reference to the relevant literature, we examine some possible managerial and organizational interventions that companies might activate in order to reduce such risks. Some of these interventions were successfully implemented by partner companies in the context of the research project.